Obca kobieta, jako zwiastun śmierci - Diakowska, Edyta (Zeszyty Wiejskie, 2011)
Folk imaginations concerning the human figure of death mostly focus on the image of a skeleton with a scythe or a female figure with a scythe. Apart from them, what is present in some regions is the image of death as an alien woman who appears in the village from nowhere and who is able to disappear suddenly – her visit is always associated with somebody’s death. In the folklore, there are also tales about meeting the death, quoted as authentic events taking place in particular villages. In Christianity, both in Catholicism and Orthodoxy, no beliefs exist that death has a shape of an ordinary woman who comes from orbis exterior. This places the analyzed belief in the earlier pre-Christian layer. In the light of the materials of the Polish Ethnographic Atlas, this folklore belief functioned in culturally backward regions of Poland.